Relações de gênero e a profissão bibliotecária na contemporaneidade: panorama nacional e os motivos da entrada masculina em curso majoritariamente feminino - Hugo Avelar Cardoso Pires (2016)
The unequal gender relations present in society determined and still determining spaces and actions of men and women. anchored in a biological determinism, professions over time became more feminist and / or male-characteristic for their work and by type of activity. The librarian profession is in the context of professions defined by the sexual division of labor, since it feminilizou mainly by the increase of its technical nature. However, there is recently increased demand for men by trainers librarians courses, especially after the 1980s the approach of Library Science with other areas such as Management and Computer Science, for example. The objetivodeste study was to investigate the reasons men choose increasingly more often the Librarianship course in Brazil, a mostly female space. From the point of view of its nature, a social survey was conducted, history and descriptive character that was divided into two stages: the first consisted of a survey of universities of the five regions of the country, about the number of graduates in Librarianship from the foundation thereof. The second stage consisted of a survey (survey) with a questionnaire sent through the tools of Google Docs for Councils Regional Library after 1980. The results of the first stage of the research indicate that although there are closer of men with the Librarianship courses , such an approach is particularly by increasing the area as a whole, given that the number of women also increases correspondingly. This fact causes an illusion that there is a reduction of the feminization of the area, which in numerical and percentage terms, it shows how a very small trend. As the survey data, found that men are attracted by the Librarianship course for various reasons, but above all by "rational reasons", such as offering evening classes, the average score cutting the lower labial and especially the provision of jobs and contests. Moreover, it was observed that there is little awareness of librarians about the gender upsetting interactions present in society and library profession.